(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
This pilot qualitative research aimed to explore the experiences of the mystical among people who hear voices, see visions and/or have other extraordinary experiences. The research method of interpretative phenomenological analysis was used in order to explore these experiences in depth. A new epistemological framework was used based on Marion’s & Steinbock’s philosophy. The participants were chosen based on specific eligibility criteria. The participants reported the importance of meaning making and of spirituality. The outcomes and possible clinical implications of psychospirituality can be understood using the tools of existential theory. Proposals for future research, epistemological issues and clinical implications will also be presented.